Health Status of Elderly Based on Daily Activities Living, Cholesterol and Uric Acid Profile in Kupang - Aldiana Astuti; Austina W. Djuma (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Uric acid and Cholesterol cause inflammation accompanied deformity knees and legs. Health problems in the elderly come from declining body cells, so the function and body endurance decreased along with increased risk factors for diseases. Prevalence of uric acid in Asia regions the lowest Papua New Guinea 1% highest Marshall Islands 85% and Indonesia 18%. Uric acid is main factor predicting kidney failure. Objective: the aim of this study was to describe the prevalence of uric acid levels and cholesterol in the pre-elderly around liliba RT 41/RW001. Method: This type of research is descriptive, the number of respondents who are willing to participate in this study is 55 people by signing an informed consent. The data were obtained by examining cholesterol levels using the POCT method, as well as consumption patterns and physical activity which were measured using a questionnaire. Results: The results showed that Cholesterol levels that consumed high-fat foods were found more in respondents who often consumed fatty foods with normal cholesterol levels of 18 people (32.7%), a high threshold of 10 people (18.2%), and high cholesterol levels of 8 people (14.5%) ). Cholesterol levels who rarely consumed meat with high cholesterol were 9 people (16.4%), and high-limit cholesterol levels were 11 people (20.0%). Cholesterol levels of respondents who had sleep duration of 6-8 hours with high cholesterol levels were 6 people (10.9%), normal cholesterol levels were 15 people (27.3%), and high limit cholesterol levels were 9 people (16.4%). Cholesterol levels of respondents who did not carry out health checks who had high cholesterol levels were 7 people (12.7%), normal cholesterol levels were 23 people (41.3%), and high limits were 19 people (34.5%). abnormal uric acid levels in 19 (34.5%) respondents. The highest uric acid levels were obtained at the age of 45-49 years (41.8%). Most abnormal uric acid levels were found in women, 12 people (21.8%). Abnormal uric acid levels were most common in respondents who consumed high-purine foods (21.8%), consumed meat (12.7%), and who always consumed high-purine vegetables (10.9%). Abnormal uric acid levels were most common in respondents who had never done strenuous physical activity as many as 13 people (23.6%), while in respondents who always did light physical activity uric acid levels were not normal as many as 15 people. In this study, it was found that 32.8% of respondents who had high uric acid levels had never had regular health checks. Conclusions: . The levels of uric acid and cholesterol in the elderly in Liliba Village RT 41/RW 001 based on age and gender, namely abnormal uric acid levels, were most commonly found in the 45-59 year age category of 10 people (18.2%) and in female as many as 12 people (21.8%). Based on age and gender, the highest cholesterol level was found in the 45-59 year age category, which was mostly found in women with normal cholesterol levels, 9 people (16.4%), high threshold, 10 people (18.2%), while high cholesterol levels as many as 4 people (7.3%).